Pengaruh Desentralisasi BPHTB Terhadap Penerimaan Asli Daerah Dan Dampaknya Terhadap Pertumbuhan Ekonomi Di Daerah Istimewa Yogyakarta - Wuku Astuti; Kristiana Sri Utami; Yuliana Endah Widyaningsih (EBBANK, 2017)
This study examines the effect of decentralization of Land Acquisition Rights (BPHTB) on Local Own Revenue (PAD) and its impact on district and / or city economic growth in Yogyakarta Special Region (DIY). The population in this research is the data of budget realization as well as the data of economic growth of regency / city in DIY. The selected sample is budget realization data and economic growth data of regencies / cities in DIY two years before decentralization and two years after decentralization of BPHTB. The normality test of data distribution is done by classical assumption test. The determination coefficient test is performed to determine the accuracy of the use of independent variables. To test the influence of independent variable to the dependent variable is done regression analysis. Whereas hypothesis testing is determined by looking at p-value. The results of statistical tests proved that the decentralization of BPHTB into local taxes will support the increase of regional PAD, and Economic Growth.